2022
DOI: 10.1332/251569120x16040852770342
|View full text |Cite
|
Sign up to set email alerts
|

Health politics? Determinants of US states’ reactions to COVID-19

Abstract: Were policy responses of the US states to the pandemic driven by partisan politics or by budgetary reasons? We show that balanced-budget rules also had an impact, mediated by the possibility of benefiting from the funds previously stored in budget stabilisation funds. State policymakers tried to square the circle by simultaneously respecting budget rules, limiting the economic impact of the social distancing measures, combating the pandemic and pandering to their political bases. Some fiscal rules have induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Recent research has shown that political factors have influenced policy responses and the public's adherence to COVID-19 regulations within the US (Adolph et al, 2020;Baccini and Brodeur, 2020;Farvaque et al, 2020) and in a cross-country context (Cheibub et al, 2020;Cronert, 2020;Sebhatu et al, 2020;Cepaluni et al, 2021c;Löblová et al, 2021). COVID-19 raised the question of an authoritarian advantage in disease response (Kavanagh and Singh, 2020), as non-democratic countries with more collectivist cultures solve coordination problems relatively easily (Gorodnichenko and Roland, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that political factors have influenced policy responses and the public's adherence to COVID-19 regulations within the US (Adolph et al, 2020;Baccini and Brodeur, 2020;Farvaque et al, 2020) and in a cross-country context (Cheibub et al, 2020;Cronert, 2020;Sebhatu et al, 2020;Cepaluni et al, 2021c;Löblová et al, 2021). COVID-19 raised the question of an authoritarian advantage in disease response (Kavanagh and Singh, 2020), as non-democratic countries with more collectivist cultures solve coordination problems relatively easily (Gorodnichenko and Roland, 2021).…”
Section: Introductionmentioning
confidence: 99%